Neurosciences cognitives et sciences de l’éducation : vers un changement de paradigme ? - France ARBOIX-CALAS (Éducation et Socialisation)
In the current context of the emergence of "neuroeducation", several authors question the interests and limits of moving from the context of a laboratory to the context, more "ecological", of a classroom. The issues raised in this research explore the possibility of an epistemological link between cognitive neuroscience and education. If the marriage between cognitive neuroscience and "ordinary" teaching still appears to be difficult and pioneering, the same is not true of linking these neurosciences with special education. We explored this historically older link to show how neuroscience research has contributed to the practices of special education. These results led us to look for epistemological common foundations to cognitive neuroscience and educational sciences, using the pedagogic triangle model (Houssaye, 1988). Our analysis suggests that these two disciplines each have a reduction that compromise the possibilities for fruitful exchange between them. However, exceeding this reduction could open avenues for fruitful dialogue in a new paradigm of research between these two disciplinary fields.